ATP2C2 Has Potential to Define Tumor Microenvironment in Breast Cancer - Liu, Jiazhou; Wei, Yuxian; Wu, Yushen; Li, Jie; Sun, Jiazheng; Ren, Guosheng; Li, Hongzhong (Frontiers in Immunology, 2021)
Tumor microenvironment (TME) plays a crucial role in the occurrence and development of breast cancer (BRCA). However, there is still a lack of comprehensive understanding about the dynamic modulation of the stromal and immune components in TME. In this study, we used ESTIMATE and CIBERSORT algorithm to analyze the number of stromal and immune components and the proportion of tumor-infiltrating immune cell (TIC) in 582 BRCA cases from gene expression omnibus (GEO) database. We employed three regression models including univariable Cox proportion, least absolute shrinkage and selection operator (LASSO) and multivariate Cox regression, and identified 7 immune-specific genes related to BRCA survival. Of 7 genes, ATPase Secretory Pathway Ca2+ Transporting 2 (ATP2C2) attracts our attention for significantly predicting prognosis of BRCA patients. Further analysis indicated that ATP2C2 expression was closely associated with the clinicopathological characteristics (age, T- and N-staging) and negatively correlated with the survival of BRCA patients. Gene Set Enrichment Analysis (GSEA) showed that the genes in the ATP2C2 low-expression group were mainly enriched in immune-related activities, and the genes in the ATP2C2 high-expression group were largely enriched in metabolic pathways. CIBERSORT analysis for the proportion of TICs revealed that ATP2C2 expression was positively correlated with T follicular helper (Tfh) cells, and negatively correlated with gamma delta (γδ) T cell, suggesting that ATP2C2 might be responsible for the preservation of immune-dominant status for TME. To sum up, this study comprehensively analyzed the TME and shed light on prognostic immune-related biomarkers for BRCA. In particular, the levels of ATP2C2 might be useful for outlining the prognosis of BRCA patients, which offered an extra insight for BRCA treatment.